Altered T-Cell Subsets are Associated with Dysregulated Cytokine Secretion of CD4+ T Cells During HIV Infection - Wang D (Dove Medical Press, 2021)
Di Wang,1,2 Yu Jiang,2 Yangzi Song,1,2 Yongqin Zeng,1 Cuilin Li,1 Xinyue Wang,2 Ying Liu,1,2 Jiang Xiao,1 Yaxian Kong,2 Hongxin Zhao1 1Clinical and Research Center of Infectious Diseases, Beijing Ditan Hospital, Capital Medical University, Beijing, People’s Republic of China; 2Beijing Key Laboratory of Emerging Infectious Diseases, Institute of Infectious Diseases, Beijing Ditan Hospital, Capital Medical University, Beijing, People’s Republic of ChinaCorrespondence: Hongxin ZhaoClinical and Research Center of Infectious Diseases, Beijing Ditan Hospital, Capital Medical University, Beijing, 100015, People’s Republic of ChinaTel +86 10-84322583Email Drzhao66@ccmu.edu.cnYaxian KongBeijing Key Laboratory of Emerging Infectious Diseases, Institute of Infectious Diseases, Beijing Ditan Hospital, Capital Medical University, Beijing, 100015, People’s Republic of ChinaTel +86 10-84322620Email kongyaxian@ccmu.edu.cnBackground: CD4+ T cells play a critical role in the regulation of immunopathogenesis in HIV infection. Previous studies have shown contradictory results of the CD4+ T-cell responses in people living with HIV (PLHIV).Methods: A cross-sectional study was performed on 40 healthy controls, 134 ART-naïve PLHIV, and 34 individuals who experienced 3-year ART with low baseline CD4 count from 4 August 2016 to 23 January 2019. We determined the frequencies of CD4+ T-cell subsets and described the cytokine secretion pattern of total and subsets of CD4+ T cells in these individuals.Results: We found that CD4+ T cells in PLHIV displayed enhanced secretion of pro-inflammation cytokines and polyfunctionality due to HIV disease progression (r = − 0.282, P = 0.0035 for IFN-γ; r = − 0.412, P = 0.0002 for TNF-α; r = − 0.243, P < 0.0001 for GM-CSF; r = − 0.252, P = 0.0093 for IFN-γ+ TNF-α+ cells). However, the altered T-cell subsets, as presented by the loss of naïve cells and expansion of memory/effector population in PLHIV, were associated with discordant results in total and subsets of CD4+ T cells. As major cytokine-producing T subsets, effector/memory CD4 subsets showed impaired cytokine production (P < 0.05). We further demonstrated that 3-year ART treatment could improve CD4 counts by increasing the pool of naïve T cells but could not restore cytokine secretion in CD4+ T-cell subsets (P < 0.05).Conclusion: These data identified the impaired capacity of cytokine secretion in CD4+ T-cell subsets due to HIV disease progression, and the altered T-cell subsets were associated with pseudo-elevation of cytokine production in total CD4+ T cells. This study collectively suggested the importance of therapies that can preserve and/or enhance the function of CD4+ T cells in strategies of HIV remission.Keywords: HIV infection, cytokines, T-cell dysfunction, T-cell subsets, inflammatory responses